False positive serum levels of (1–3)-ß-D-Glucan after infusion of intravenous immunoglobulins and time to normalisation. Issue 2 (February 2018) - Egger, M.; Prüller, F.; Raggam, R.; Divjak, M.K.; Kurath-Koller, S.; Lackner, H.; Urban, C.; Strenger, V.
Highlights: Immunoglobulin preparations (IVIG) contain high amounts of (1–3)-ß-D-Glucan (BDG). IVIG administration leads to false positive BDG serum levels in most patients. After IVIG administration BDG levels may remain elevated for more than 2 weeks. 3 weeks after IVIG administration, BDG serum levels normalize in all patients. Summary: Objectives: (1–3)-ß-D-Glucan (BDG) is a marker for invasive fungal diseases (IFD). Administration of intravenous immunoglobulin preparations (IVIG) has been reported to lead to false positive BDG serum levels >80 pg/ml. The aim of the study was to determine the time interval between IVIG infusion and normalisation of BDG serum levels. Methods: In 22 paediatric haemato-/oncologic patients, we analysed 92 BDG serum levels obtained within 4 weeks after IVIG administration (0.5 to 1 g/kg body weight), correlated them to 54 IVIG episodes and compared them to 76 BDG levels obtained in 29 patients without IVIG administration in the 4 weeks prior to BDG analyses (control group). Results: BDG peak levels within 3 days after IVIG ranged from 21.47 to 660.38 (median 201.4) pg/ml. BDG serum levels at 7, 14 and 21 days (+/−1 day each) after IVIG infusion were significantly higher than BDG serum levels in the control group (p < 0.001 each). By days 7, 14, and 21 (+/−1 day each) after IVIG infusion, BDG serum levels have normalized (<80 pg/ml) in 64.0%, 76.5% and 100%, respectively. Conclusions: IVIG administration leads to false positive BDG levels in the vast majority of patients. Elevated BDG levels may be detectable for more than two weeks after IVIG administration, while BDG levels normalized within 3 weeks in all patients. Therefore, BDG should not be used to diagnose IFD within three weeks after IVIG administration.